ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK DALAM MERESPON SURAT HIMBAUAN TERHADAP KEPATUHAN PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN (Studi Pada Kantor Pelayanan Pajak Pratama Batu) - Subagiyo, Eviany Kusmanasari (Jurnal Mahasiswa Perpajakan, 2014)
A kind of law enforcement in taxation is the appeal of tax payment to induce the submission of tax annual report (SPT). Letter of Appeal is a letter released by Tax Service Office based on internal investigation to ask for clarification from Taxpayers about the estimation of failure to obey tax affair pursuant to predetermined tax regulationsâ€. The objective of research is to understand the influence of variables of Sanction, Taxpayers Awareness, Service, and Supervision on the Obedience to Submit Tax Annual Report. Research method is explanatory research which attempts to show a causal relationship between research variables through hypothesis testing. Based on the result of Multiple Linear Regression analysis, it is indicated that the variables of Taxpayers Awareness, Service and Supervision have positive and significant influence on the Obedience to Submit Tax Annual Report. It may be suggested that predetermined tax regulations must be obeyed and highly attended by taxpayers. Keywords: Sanction, Taxpayers Awareness, Service, Supervision, and The Obedience to Submit Tax Annual Report